2019
DOI: 10.1111/his.13854
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of recurrences and high‐grade forms of polymorphous adenocarcinoma

Abstract: Aims Polymorphous adenocarcinoma (PAC) usually follows an indolent course, but some cases may show recurrences and high‐grade features. The genetic events associated with recurrences and high‐grade versions are yet to be defined. Our aim was to determine the genetic underpinning of recurrent PACs of the salivary gland and the repertoire of somatic genetic alterations in cases with high‐grade histology. Methods and results Four PACs from three patients, including one case with matching primary and recurrent tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…High-grade transformation (HGT) has been reported in several salivary gland malignancies and even in PAC. [11][12][13] In this report, the tumor consisted of areas predominately solid nests of high-grade carcinoma with central necrosis arranged in lobules delineated with prominent stromal septa and areas of classic/ conventional CASG morphologic features. The biologic significance of HGT in CASG is yet to be understood.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…High-grade transformation (HGT) has been reported in several salivary gland malignancies and even in PAC. [11][12][13] In this report, the tumor consisted of areas predominately solid nests of high-grade carcinoma with central necrosis arranged in lobules delineated with prominent stromal septa and areas of classic/ conventional CASG morphologic features. The biologic significance of HGT in CASG is yet to be understood.…”
Section: Discussionmentioning
confidence: 62%
“…The presence of a high‐grade component led us to carry out a salivary NGS fusion panel analysis to confirm the diagnosis. High‐grade transformation (HGT) has been reported in several salivary gland malignancies and even in PAC 11–13 . In this report, the tumor consisted of areas predominately solid nests of high‐grade carcinoma with central necrosis arranged in lobules delineated with prominent stromal septa and areas of classic/conventional CASG morphologic features.…”
Section: Discussionmentioning
confidence: 69%
“…ARID1A mutations have been very well characterized in ovarian clear cell carcinoma and endometrioid adenocarcinoma [11], whereas aberrations in ARID1A have been described only very rarely in salivary gland tumors: a ARID1A-PRKD1 fusion has been reported in cribriform adenocarcinoma of salivary gland origin by Weinreb et al [12]. Moreover, Sebastiao et al recently showed a terminating p.Q288Pfs*71 frameshift ARID1A deletion in a polymorphous adenocarcinoma [13]. Terminating mutations and frameshift mutations leading to early termination of ARID1A protein translation and thereby to a loss of function, have been described previously in salivary gland carcinomas (12/114 sequenced salivary gland tumors) encompassing in addition salivary duct carcinoma (2/18 samples) and adenoid cystic carcinoma (10/73 samples) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The definition and terminology of PAC have changed with the times. PAC has long been called polymorphous low‐grade adenocarcinoma (PLGA); however, the term “low‐grade” was eliminated in the current WHO Classification of Head and Neck Tumors published in 2017 because of the presence of rare aggressive cases 1,4–6 . On the other hand, a tumor entity named cribriform adenocarcinoma of salivary gland (CASG) was proposed as an independent tumor type from PAC 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…PAC has long been called polymorphous low-grade adenocarcinoma (PLGA); however, the term "low-grade" was eliminated in the current WHO Classification of Head and Neck Tumors published in 2017 because of the presence of rare aggressive cases. 1,[4][5][6] On the other hand, a tumor entity named cribriform adenocarcinoma of salivary gland (CASG) was proposed as an independent tumor type from PAC. 7,8 CASG has a propensity to occur at the base of tongue, with a lobulated architecture, a predominant solid, microcystic and cribriform growth pattern, and a uniform type of tumor cells with ground-glass, optically clear nuclei.…”
Section: Introductionmentioning
confidence: 99%